Pathological changes of the skin and the oral mucosa during pregnancy – part II - Szlachcic, Aleksandra; Pytko-Polończyk, Jolanta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
The specific physiological or pathological changes of the skin and mucous membranes can occur during pregnancy. Also the effect of pregnancy on some skin disorders is highly variable and are not predictable, some of the skin conditions may improve while others are aggravated. The changes in the course of the skin and mucous membranes disorders during pregnancy were presented, based on data from literature. The choice of the therapy during pregnancy is an important management option.